Mapping Joyful Art Learning Strategies to Strengthen Students”™ Deep Understanding in Elementary Schools - Prasetyo, Alfian Eko Widodo Adi; Setyaningrum, Ikha Sulis; Wulandari, Dewi; Budy, Elinta (Jurnal Tarbiyatuna, 2025)
Developing students”™ deep understanding through meaningful learning experiences requires instructional approaches that are both engaging and emotionally supportive. This study aims to map the implementation of joyful art learning strategies in elementary schools and analyze how such strategies contribute to students”™ deep understanding. A descriptive qualitative approach was employed, involving classroom observations, teacher interviews, and document analysis of instructional materials. The data were analyzed through thematic coding to identify patterns in learning activities and their cognitive implications. The findings reveal that joyful art learning is implemented through experiential activities, creative exploration, collaborative tasks, and reflective discussions, which encourage students to express ideas, interpret meaning, and construct conceptual understanding. These strategies were found to strengthen deep understanding by promoting active engagement, imagination, and higher-level cognitive processes. However, the implementation still faces challenges, including insufficient learning time, limited art learning facilities, and variability in teachers”™ pedagogical competence. This study highlights the importance of integrating joyful learning principles into art education to create emotionally supportive learning environments and to enhance cognitive depth in elementary students.